Copper ion/gallic acid MOFs-laden adhesive pomelo peel sponge effectively treats biofilm-infected skin wounds and improves healing quality - Yang, Jianqiu; Huang, Zhenzhen; Tan, Jiang; Pan, Jingye; Chen, Shixuan; Wan, Wenbing (Bioactive materials, 2024)
Bacterial infection and scar formation remain primary challenges in wound healing. To address these issues, we developed a decellularized pomelo peel (DPP) functionalized with an adhesive PVA-TSPBA hydrogel and antibacterial gallic acid/copper MOFs. The hybrid wound dressing demonstrates favorable biocompatibility. It does not impede the proliferation of fibroblasts or immune cells and can stimulate fibroblast migration, endothelial angiogenesis, and M2 macrophage polarization. Additionally, the dressing can scavenge reactive oxygen species (ROS) and provide antioxidant effects. Furthermore, DPP + MOF@Gel effectively inhibits the viability of S. aureus and E. coli in vitro and in vivo. The histological observations revealed enhanced granulation tissue formation, re-epithelialization, and angiogenesis in the DPP + MOF@Gel group compared to other groups. The local immune response also shifted from a pro-inflammatory to a pro-regenerative status with DPP + MOF@Gel treatment. The skin incision stitching experiment further exhibits DPP + MOF@Gel could reduce scar formation during wound healing. Taken together, the hybrid DPP + MOF@Gel holds great promise for treating bacteria-infected skin wounds and inhibiting scar formation during wound healing.Bacterial infection and scar formation remain primary challenges in wound healing. To address these issues, we developed a decellularized pomelo peel (DPP) functionalized with an adhesive PVA-TSPBA hydrogel and antibacterial gallic acid/copper MOFs. The hybrid wound dressing demonstrates favorable biocompatibility. It does not impede the proliferation of fibroblasts or immune cells and can stimulate fibroblast migration, endothelial angiogenesis, and M2 macrophage polarization. Additionally, the dressing can scavenge reactive oxygen species (ROS) and provide antioxidant effects. Furthermore, DPP + MOF@Gel effectively inhibits the viability of S. aureus and E. coli in vitro and in vivo. The histological observations revealed enhanced granulation tissue formation, re-epithelialization, and angiogenesis in the DPP + MOF@Gel group compared to other groups. The local immune response also shifted from a pro-inflammatory to a pro-regenerative status with DPP + MOF@Gel treatment. The skin incision stitching experiment further exhibits DPP + MOF@Gel could reduce scar formation during wound healing. Taken together, the hybrid DPP + MOF@Gel holds great promise for treating bacteria-infected skin wounds and inhibiting scar formation during wound healing.